Utilization of Kepok Banana Peels Fermentation on Rabbits Pellet Feed - T. H. Wahyuni; G. A. W. Siregar; Santoso, I. (Jurnal Peternakan Integratif, 2022)
The need for rabbit pellets is increasing along with the increasing maintenance of rabbits in North Sumatra. This study aims to determine the feed consumption (FC), avarage daily gain (ADG), and feed conversion ratio (FCR), of male local rabbits given fermented kepok banana peel (KBP) pellets. The fermentation used in this study was using local microorganisms based on KBP. This research was conducted by Dr. Hamza No. 5 North Sumatra Province from October 2020 to December 2020.The research design was used a randomized block design (RBD) with 3 treatments, 3 groups and each group consisted of 3 rabbits so that 27 male local rabbits were obtained. The treatments were P0 = 40% KBP without fermentation in pellets, P1 = 40% fermented KBP in pellets and P2 = 60% fermented KBP in pellets. Determination of groups based on body weight with the following groupings: K1: 418 g - 458 g, K2: 459 g - 499 g, and K3: 500 g - 540 g.The results of P0, P1 and P2 showed that the value of FC (g / head / day) were 83.76; 84.58; and 86.83 respectively. TheADG value (g / head / day) were 11.47; 12.79; and 15.01 respectively. The FCR value were 7.45; 6.78; and 5.93 respectively. The conclusion shows that the utilization of fermented KBP up to a level of 60% in the pellets is more efficient to use to increase Feed Consumption, Average Daily Gain, Income OverFeed Cost and reduce Feed Convertion Ratio of male local rabbits.